Alfred N. Whitehead on process philosophy and theology: Cosmos and Kenosis of Divinity - Monserrat, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The modern dialogue between religion and science has to take into account the process philosophy and theology. Science, for the authors in this movement, is the thoughts of Whitehead: a science of the first half of the 20th century, understood according to a certain philosophy of process proposed by Whitehead (which is not only science but a risky, complex and subtle philosophy based on science). In this article we are only referring to one of the episodes in the philosophy of process: that which is characterised by Alfred Whitehead and some of his followers in the creation of the philosophy-theology of process in the Anglo-Saxon, and especially American world. Our intention is to present an evaluation and discussion that is oriented towards what we feel is important: the discussion of his cosmology and theology of kenosis. However, in order to do this we need to make our points of view fit in with a line of thought that makes reference to his metaphysics and philosophy of religion. Whitehead does not question the world at this ultimate level of «primary causality» (in its absoluteness and necessity) given that the world is eternal: that is absolute and necessary. Whitehead’s problem is that of explaining the system of «secondary causes», because they do not seem to constitute a system that is sufficient but rather introduce the reference of God and an element of the world that contributes to what the world is from the inside. God, for Whitehead, is also not responsible for Evil because he does not create the world; on the contrary, he is subject to the conditions established in the same world and tries to overcome it and guide it to perfection. Kenosis or divine auto-limitation, for Whitehead, is only partial because a large part of divine limitation is imposed by the nature of the eternal world (not created) of which God form a part.